Familial Colloid Cysts of the Third Ventricle: Case Report and Literature Review - Calderón, Carlos (Asian J Neurosurg, 2020)
Colloid cysts of the third ventricle are rare lesions. To our knowledge, only 23 familial cases of colloid cysts have been reported in the literature. The country of origin of the patients with familial cases had not been previously studied as a group. A 49-year-old female patient from Puerto Rico and her 21-year-old daughter underwent surgical resection for colloid cysts within a period of 5 years. The daughter presented with symptomatic hydrocephalus, while the mother only had mild chronic headaches. The occurrence of a colloid cyst in this family prompted us to perform a literature review and tabulate all the familial cases. This report presents the 24(th) case of a familial colloid cyst, and the fourth involving a mother and daughter. Australia is the country with the largest amount of reported cases. For smaller countries such as Sweden and Finland, two cases had been reported for each of them. Due to the unlikely probability of familial colloid cyst occurring at random, a genetic component is likely to be involved. The occurrence of several reports from patients from Australia, Finland, Sweden, and Puerto Rico where the population is smaller or more segregated may also suggest a genetic inheritance. Screening of first-degree-related subjects is recommended for families in which two or more members are affected. The presence of a colloid cyst in a twin mandates neuroimaging in the other twin, as there are five familial cases in twins reported in the literature.